Cadaverine Production From L-Lysine With Chitin-Binding Protein-Mediated Lysine Decarboxylase Immobilization - Zhou, Ning; Zhang, Alei; Wei, Guoguang; Yang, Sai; Xu, Sheng; Chen, Kequan; Ouyang, Pingkai (Frontiers in Bioengineering and Biotechnology, 2020)
Lysine decarboxylase (CadA) can directly convert L-lysine to cadaverine, which is an important platform chemical that can be used to produce polyamides. However, the non-recyclable and the poor pH tolerance of pure CadA hampered its practical application. Herein, a one-step purification and immobilization procedure of CadA was established to investigate the cadaverine production from L-lysine. Renewable biomass chitin was used as a carrier for lysine decarboxylase (CadA) immobilization via fusion of a chitin-binding domain (ChBD). Scanning electron microscopy, laser scanning confocal microscopy, fourier transform infrared spectra, elemental analysis, and thermal gravimetric analysis proved that the fusion protein ChBD-CadA can be adsorbed on chitin effectively. Furthermore, the fusion protein (ChBD-CadA) existed better pH stability compared to wild CadA, and kept over 73% of the highest activity at pH 8.0. Meanwhile, the ChBD-CadA showed high specificity toward chitin and reached 93% immobilization yield within 10 minutes under the optimum conditions. The immobilized ChBD-CadA (I-ChBD-CadA) could efficiently converted L-lysine at 200.0 g/L to cadaverine at 135.6 g/L in a batch conversion within 120 min, achieving a 97% molar yield of the substrate L-lysine. In addition, the I-ChBD-CadA was able to be reused under a high concentration of L-lysine and retained over 57% of its original activity after 4 cycles of use without acid addition to maintain pH. These results demonstrate that immobilization of CadA using chitin-binding domain has the potential in cadaverine production on an industrial scale.